Laitan: The Making of a Chan Cave Temple Site in Sichuan - Howard, Angela F. (Journal of Chan Buddhism, 2020)
Laitan 淶灘 is a monumental site in Sichuan, built during the Song Dynasty (960–1279), located approximately 69 km northwest of present day Chongqing. It is the only site in China whose sculpture derives from a comprehensive records of Chan developments. A crowded gathering of famous Chan prelates and anonymous personages of all sizes animate the cave’s walls; they were inspired both by the early Chan phase in Sichuan and the subsequent Song outside Sichuan.